DIGITAL GAME-BASED LIT-KEW MODULE FOR KEMAS PRESCHOOLERS: A MODIFIED NOMINAL GROUP TECHNIQUE APPROACH - Rani, Norhashimah Abdul; Zain, Azizah; Basir, Jamilah Mohd; Hassan, Noor Asiah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study aims to design a Digital Game-Based LIT-KEW Module tailored for TABIKA preschool children, aligned with the Malaysian National Preschool Standard Curriculum (KSPK 2017). The primary objective was to obtain expert consensus on the essential components of the module through the Modified Nominal Group Technique (Modified NGT). Nine experts comprising early childhood education lecturers, experienced TABIKA teachers, and language specialists participated in the session. Consensus analysis revealed agreement levels exceeding 80% for learning objectives (83%), financial literacy content covering monetary value, spending, and saving (86%), and game-based teaching strategies (82%). Meanwhile, appropriate hardware and engaging digital media reached 78% and 81% agreement, respectively. These results confirm the robustness of the module’s design, which is grounded in constructivist learning theory and informed by Maslow’s hierarchy of needs to ensure holistic and meaningful learning. The study contributes a novel framework for contextual, interactive, and developmentally appropriate digital financial literacy education at the preschool level. Findings underscore practical implications for curriculum developers and early childhood policymakers, who may consider integrating digital financial literacy into preschool education as a foundation for lifelong financial competence.